Enhancing Vocabulary Acquisition in B2 Level Students through Diverse Exercise Modalities and Reading Activities (Eurasian Scientific Herald, 2023)
This scientific article explores innovative approaches to elevate the vocabulary proficiency of B2 level students by integrating various exercises and activities centered around reading. The B2 level, as defined by the Common European Framework of Reference for Languages, signifies an intermediate language proficiency, and this stage is crucial for language learners aiming to advance towards higher competency. Recognizing the significance of a robust vocabulary foundation, we investigate how diverse exercises coupled with focused reading can offer a multifaceted and effective strategy for vocabulary enhancement. This study aims to provide educators and learners with practical insights into optimizing language acquisition at the intermediate level.